Human induced pluripotent stem cells for studying mitochondrial diseases in the heart. Issue 14 (11th July 2022) - Caudal, Arianne; Ren, Lu; Tu, Chengyi; Wu, Joseph C.
Abstract : Mitochondrial dysfunction is known to contribute to a range of diseases, and primary mitochondrial defects strongly impact high‐energy organs such as the heart. Platforms for high‐throughput and human‐relevant assessment of mitochondrial diseases are currently lacking, hindering the development of targeted therapies. In the past decade, human‐induced pluripotent stem cells (iPSCs) have become a promising technology for drug discovery in basic and clinical research. In particular, human iPSC‐derived cardiomyocytes (iPSC‐CMs) offer a unique tool to study a wide range of mitochondrial functions and possess the potential to become a key translational asset for mitochondrial drug development. This review summarizes mitochondrial functions and recent therapeutic discoveries, advancements and limitations of using iPSC‐CMs to study mitochondrial diseases of the heart with an emphasis on cardiac applications. Abstract : Mitochondrial dysfunction contributes to a range of diseases, with primary mitochondrial defects strongly impacting high‐energy organs such as the heart. Here, we review how patient‐derived induced pluripotent stem cells (iPSCs) carrying certain mitochondrial mutations can be exploited to generate human iPSC‐derived cardiomyocytes and to study mitochondrial diseases of the heart.